Implementasi Otonomi Daerah Terhadap Pelayanan Publik Dan Tata Kelola Pemerintahan - Dadang Hidayat; Dedi Mulyadi; Aji Mulyana (Badan Penerbit STIEPARI Press, 2025)
This study focuses on the Implementation of Regional Autonomy in relation to Public Services and Governance in Cianjur Regency. The objective of this research is to analyze the strategies implemented by the Cianjur Regional Government to enhance public transparency and accountability, as well as to evaluate the effectiveness of the implementation of Regional Regulation Number 9 of 2017. This research employs a qualitative method with a descriptive-analytical approach. Data were collected through in-depth interviews with local government officials, legislative members, and community representatives, as well as through document studies of policies and the implementation of the regulation. The findings indicate that the strategies implemented include the digitalization of public services, capacity building of civil servants in information management, and the strengthening of internal and external oversight mechanisms. To further improve public transparency and accountability, the Cianjur Regional Government needs to accelerate digital transformation in information provision and enhance public awareness of regulations.